Communication lifestyle of Indonesian and Malaysia students during the corona virus 19 pandemic - Farida Nurfalah; Muhammad Nuruzzaman; Jamilah Ahmad (Jurnal Kajian Komunikasi, 2022)
Several ways occur in lifestyle 2022 to protect themselves from coronavirus transmission. The research objectives are as follows: To find out the activities of Indonesia Students during the COVID-19 Pandemic, to find out the interests of Indonesian students during the COVID-19 Pandemic, to find out the opinions of Indonesian students during the COVID-19 Pandemic. The research method uses a descriptive approach with the type of qualitative research. The research subjects based on the purposive technique were seven students. The results; Activities of Indonesian students are mainly carried out at home by government regulations by limiting interaction activities with family, friends, and neighbors. Their attention to government policies, studying while doing business, interacting with friends, and entertainment. When making decisions, they are more concerned about money, benefits, and health and are confident in the decisions they make. Student opinions facing the covid pandemic situation are more healthy, grateful, and able to help each other, maintain SOPs, stay productive, the government pays attention to the people, and families always maintain cleanliness and health. Thus, most student activities during the Covid-19 pandemic are carried out at home by limiting interaction activities. Students have attention to government policies, study while doing business, interact with friends, and entertainment to relieve boredom. Students are concerned with maintaining health, being grateful and helping each other. Efforts are being made to maintain SOPs, stay productive, and maintain health protocols. Efforts that need to be made by the government are by listening to the voices of the community and helping the affected communities, while the hope that families need to always maintain cleanliness and provide mutual support, respecting the things around them.